Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery
The use of a specific positive electrode active material composition and structure in lithium secondary batteries addresses the issues of resistance and oxygen release rates, enhancing battery safety and performance.
Patent Information
- Application Number
- JP2023154140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-02
AI Technical Summary
Lithium secondary batteries face challenges in reducing resistance and oxygen release rates during charging, which can lead to increased risk of ignition due to abnormal heat generation.
A positive electrode active material composed of Li, Ni, and element X, where X is selected from a group of elements, with specific compositional ratios and crystal structure characteristics that reduce resistance and oxygen release rates.
The proposed solution effectively decreases the resistance and oxygen release rate of lithium secondary batteries, thereby reducing the risk of ignition and improving overall battery performance.
Smart Images

Figure 2025046014000003 
Figure 2025046014000004 
Figure 2025046014000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, and a lithium secondary battery. [Background technology]
[0002] In a lithium secondary battery, the positive electrode is made using a positive electrode active material containing, for example, a lithium metal composite oxide.
[0003] Conventionally, various positive electrode active materials have been proposed to improve the performance of lithium secondary batteries (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2018 / 043190A1 Summary of the Invention [Problem to be solved by the invention]
[0005] In order to improve the performance of lithium secondary batteries, it is required to reduce the resistance and the rate at which oxygen is released when the battery is in a charged state.
[0006] Therefore, an object of the present invention is to provide a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, and a lithium secondary battery, which are capable of reducing the resistance of the lithium secondary battery and reducing the oxygen release rate when oxygen is released in a charged state. [Means for solving the problem]
[0007] The present invention has the following aspects. [1] The composition contains Li, Ni, and element X, The element X is at least one element selected from the group consisting of Co, Al, Mn, Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, and B, having a NaFeO2-type crystal structure, a positive electrode active material for a lithium secondary battery, wherein the amount of substance of Li [Li], the amount of substance of Ni [Ni], and the amount of substance of element X [X] satisfy the relationships shown in the following (Formula A1) to (Formula A3), in the spectrum of powder X-ray diffraction using CuKα radiation, the interplanar spacing d obtained from the diffraction peak A attributed to the (110) plane satisfies the relationship shown in the following (Formula B), the full width at half maximum WA of the diffraction peak A and the full width at half maximum WB of the diffraction peak B attributed to the (003) plane satisfy the relationship shown in the following (Formula C), a positive electrode active material for a lithium secondary battery. [Li]:[Ni]:[X]=a:(1-b):b …(Formula A1) 1.0≦a≦1.2 …(Formula A2) 0<b≦0.3 …(Formula A3) 1.4325Å≦d≦1.4355Å …(Formula B) 1.6≦WA / WB≦2.3 …(Formula C) [2] the full width at half maximum WB of the diffraction peak B satisfies the relationship shown in the following (Formula D), the positive electrode active material for a lithium secondary battery according to [1]. 0.16°≦WB≦0.18° …(Formula D) [3] in the spectrum of the powder X-ray diffraction, the height HB of the diffraction peak B and the height HC of the diffraction peak C attributed to the (006) plane satisfy the relationship shown in the following (Formula E), the positive electrode active material for a lithium secondary battery according to [1] or [2]. 3.0≦HB / HC≦4.5 …(Formula E) [4] the average primary particle diameter PS satisfies the relationship shown in the following (Formula F), The positive electrode active material for a lithium secondary battery according to any one of [1] to [3]. 0.05μm≦PS≦1μm…(Formula F) [5] 50% cumulative volumetric grain size D 50 satisfies the relationship shown in the following (Equation G), [1] to [4], wherein the positive electrode active material for a lithium secondary battery is 5μm≦D 50 ≦30μm…(Formula G) [6] 90% cumulative volumetric grain size D 90 and 10% cumulative volumetric grain size D 10 and satisfy the relationship shown in the following (Equation H), [1] to [5]. A positive electrode active material for a lithium secondary battery according to any one of [1] to [5]. 1.6≦D 90 / D 10 ≦3.2 …(Formula H) [7] [1] to [6], which has a positive electrode active material for a lithium secondary battery according to any one of the above. Positive electrode for lithium secondary batteries. [8] [7] The positive electrode for a lithium secondary battery according to the present invention is provided. Lithium secondary battery. Effect of the Invention
[0008] According to the present invention, it is possible to provide a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, and a lithium secondary battery, which are capable of reducing the resistance of the lithium secondary battery and reducing the oxygen release rate when oxygen is released in a charged state. [Brief description of the drawings]
[0009] [Figure 1A] FIG. 1A is a diagram showing an example of a thermogravimetric curve (TG curve). [Figure 1B] FIG. 1B is a graph showing a curve of the oxygen release rate obtained by differentiating the thermogravimetric curve (TG curve) with respect to time t. [Diagram 2]FIG. 2 is a schematic diagram showing an example of a lithium secondary battery. [Diagram 3] FIG. 3 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An example of an embodiment of the present invention will now be described.
[0011] In this specification, abbreviations are used for terms as appropriate. Specifically, metal composite compounds are indicated by the abbreviation "MCC" (Metal Composite Compound). Cathode active material for lithium secondary batteries is indicated by the abbreviation "CAM" (Cathode Active Material for lithium secondary batteries). In addition, "Ni" and "Li" indicate nickel element and lithium element, not nickel metal element and lithium metal element. The same applies to other elements such as Co and Mn. For example, when a numerical range is described as "5-15 μm", it means a range from 5 μm to 15 μm, including the lower limit of 5 μm and the upper limit of 15 μm. A lithium secondary battery means a battery in which an electrolyte (such as a non-aqueous electrolyte or a solid electrolyte) is disposed between a positive electrode and a negative electrode, and charging and discharging are performed by lithium ions moving between the positive electrode and the negative electrode via the electrolyte.
[0012] [A]CAM In this embodiment, the CAM may include a coating layer that includes a lithium compound (e.g., LiOH, Li2CO3) or Li and at least one element selected from the group consisting of Nb, Ge, Si, P, Al, W, Ta, Ti, S, Zr, Zn, V, and B.
[0013] When the CAM is used in a lithium secondary battery, the resistance can be reduced and the oxygen release rate when oxygen is released in a charged state can be reduced. When a lithium secondary battery is charged and heated in a state in which lithium ions are desorbed from the crystal structure of the CAM, a change in the crystal structure (for example, a change from a layered structure to a spinel structure) and thermal decomposition due to reduction of Ni can occur, which may result in the release of oxygen from the CAM. The released oxygen burns the electrolyte and is likely to cause the battery to ignite. When a CAM with a low thermal decomposition rate and a reduced oxygen release rate is used, the possibility of the battery igniting can be reduced even if the battery generates abnormal heat due to an internal short circuit.
[0014] [A-1] Crystal structure CAM has a NaFeO2-type crystal structure, which is a layered structure in which Li is arranged between two-dimensional layers formed mainly of Ni and oxygen elements, and Li can easily diffuse in the layered structure, thereby reducing the resistance of lithium secondary batteries.
[0015] The crystal structure of CAM can be confirmed by powder X-ray diffraction measurement using an X-ray diffractometer (for example, Ultima IV manufactured by Rigaku Corporation).
[0016] [A-2] Composition The CAM contains at least Li, Ni, and an element X in its composition.
[0017] Here, the element X is at least one element selected from the group consisting of Co, Mn, Al, Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, and B. The element X is preferably at least one element selected from the group consisting of Co, Mn, Al, Mg, Ca, W, Nb, Ti, Zr, and B. In addition, the element X is preferably composed of at least one element selected from the group consisting of Co, Al, and Mn, and at least one element selected from the group consisting of Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, and B.
[0018] The molar amount of Li, [Li], the molar amount of Ni, [Ni], and the molar amount of element X, [X], contained in the CAM satisfy the relationships shown in the following (Equation A1) to (Equation A3) (a = [Li] / ([Ni] + [X])).
[0019] [Li]:[Ni]:[X] = a:(1 - b):b …(Equation A1) 1.0 ≤ a ≤ 1.2 …(Equation A2) 0 < b ≤ 0.3 …(Equation A3)
[0020] By using a CAM that satisfies the relationships shown in (Equation A1) to (Equation A3), the resistance of the lithium secondary battery can be reduced, and the oxygen evolution rate in the charged state can be reduced. It is more preferable that the CAM satisfies the relationship shown in the following (Equation A2a), even more preferable that it satisfies the relationship shown in the following (Equation A2b), and particularly preferable that it satisfies the relationship shown in the following (Equation A2c).
[0021] 1.00 ≤ a ≤ 1.15 …(Equation A2a) 1.03 ≤ a ≤ 1.12 …(Equation A2b) 1.05 ≤ a ≤ 1.11 …(Equation A2c)
[0022] Incidentally, the composition of the CAM is measured using, for example, an ICP emission spectrometer (such as Optima7300 manufactured by PerkinElmer, Inc.). The measurement of the composition is carried out by dissolving the sample in an acid or an alkali according to the element to be measured.
[0023] [A - 3] Lattice plane spacing d of (110) plane In the spectrum of the powder X - ray diffraction measurement using CuKα rays, the lattice plane spacing d obtained from the diffraction peak A attributed to the (110) plane of the CAM satisfies the relationship shown in the following (Equation B).
[0024] 1.4325 Å ≤ d ≤ 1.4355 Å …(Equation B)
[0025] d is preferably 1.4328 Å or more, more preferably 1.4330 Å or more. d is preferably 1.4353 Å or less, more preferably 1.4350 Å or less, and even more preferably 1.4347 Å or less. d is preferably 1.4328-1.4353 Å, more preferably 1.4330-1.4350 Å, and even more preferably 1.4330-1.4347 Å.
[0026] In the CAM having d in the above range, the (110) plane parallel to the two-dimensional spreading direction of the layered structure has an appropriate interplanar spacing in the layered structure, that is, Ni, element X, and oxygen element forming one layer have an appropriate bond distance, and the bonds between Ni, element X, and oxygen element are in a stabilized state. Therefore, it is considered that the resistance of the lithium secondary battery can be reduced and the oxygen release rate in a charged state can be reduced.
[0027] The lattice spacing d can be determined by powder X-ray diffraction measurement using an X-ray diffractometer (Rigaku Corporation, SmartLab). Specifically, CAM powder is loaded onto a dedicated substrate, and then a powder X-ray diffraction spectrum is obtained by measuring under the following conditions using a Cu-Kα radiation source.
[0028] Diffraction angle 2θ: 10~90° Sampling width: 0.02°
[0029] The powder X-ray diffraction spectrum is then analyzed using the integrated powder X-ray analysis software (JADE).
[0030] Then, d can be calculated from the diffraction peak A assigned to the (110) plane. d can be calculated based on Bragg's law: 2d sinθ=nλ (where θ is the diffraction angle (rad) and λ is the wavelength (CuKα radiation)).
[0031] [A-4] Relationship between the half-width WA of the diffraction peak A of the (110) plane and the half-width WB of the diffraction peak B of the (003) plane (WA / WB) In the spectrum of the powder X-ray diffraction measurement of CAM, the half-width WA of the diffraction peak A assigned to the (110) plane and the half-width WB of the diffraction peak B assigned to the (003) plane satisfy the relationship shown in the following (Formula C).
[0032] 1.6≦WA / WB≦2.3…(Formula C)
[0033] WA / WB is preferably 1.65 or more, and more preferably 1.70 or more. WA / WB is preferably 2.30 or less, and more preferably 2.20 or less. WA / WB is preferably 1.65-2.30, and more preferably 1.70-2.20.
[0034] The half-width of the diffraction peak is related to the size of the crystallite, and the smaller the half-width, the larger the crystallite. When WA / WB is in the above range, it indicates that the (003) plane, which is the direction in which the layers are stacked in the layered structure, is growing moderately, and there are an adequate number of reaction sites where lithium ions can be inserted and removed from the crystal structure, which reduces the resistance of the lithium secondary battery.
[0035] The WA / WB ratio is calculated by determining the half-width WA of the diffraction peak A assigned to the (110) plane and the half-width WB of the diffraction peak B assigned to the (003) plane from the powder X-ray diffraction spectrum obtained above.
[0036] [A-5]WB It is preferable that the WB of the CAM satisfies the relationship shown in the following (Formula D).
[0037] 0.16°≦WB≦0.18°…(Formula D) WB is preferably 0.161° or more, and more preferably 0.163° or more. WB is preferably 0.179° or less, and more preferably 0.177° or less. WB is preferably 0.161-0.179°, and more preferably 0.163-0.177°.
[0038] The diffraction peak B is the strongest diffraction peak in CAM. In CAM with WB in the above range, the entire crystal having a layered structure is grown appropriately, so that the resistance of the lithium secondary battery can be reduced and the oxygen release rate in the charged state can be reduced.
[0039] [A-6] Relationship between the height HB of the diffraction peak B of the (003) plane and the height HC of the diffraction peak C of the (006) plane (HB / HC) In the spectrum obtained by powder X-ray diffraction measurement, it is preferable that the height HB of the diffraction peak B and the height HC of the diffraction peak C assigned to the (006) plane satisfy the relationship shown in the following (Formula E).
[0040] 3.0≦HB / HC≦4.5…(Formula E)
[0041] HB / HC is preferably 3.1 or more, more preferably 3.3 or more. HB / HC is preferably 4.4 or less, more preferably 4.2 or less. HB / HC is preferably 3.1-4.4, more preferably 3.3-4.2.
[0042] Both the (003) and (006) planes are crystal planes in the direction in which the layered structure is stacked. When the HB / HC ratio is within the above range, the stacking of the layered structure has regularity over a wider range, and there are fewer defects and irregularities in the CAM crystals, so that the resistance of the lithium secondary battery can be reduced, and the oxygen release rate in the charged state can be reduced.
[0043] The above HB and HC are determined from the powder X-ray diffraction spectrum obtained above.
[0044] [A-7] Average primary particle size PS CAM is a powder containing a plurality of particles. CAM may be composed only of secondary particles formed by agglomeration of primary particles, or may contain primary particles and secondary particles formed by agglomeration of a plurality of primary particles.
[0045] The above-mentioned "primary particles" are particles that have no grain boundaries when the CAM is observed at a magnification of 1000-30000 times using a microscope (such as a scanning electron microscope). The above-mentioned "secondary particles" are aggregates of the primary particles.
[0046] In this case, it is preferable that the average primary particle diameter PS, which is the diameter of the primary particles contained in the CAM, satisfies the relationship shown in the following (Formula F).
[0047] 0.05μm≦PS≦1μm…(Formula F)
[0048] PS is preferably 0.1 μm or more, more preferably 0.2 μm or more. PS is preferably 0.8 μm or less, more preferably 0.7 μm or less. PS is preferably 0.1-0.8 μm, more preferably 0.2-0.7 μm.
[0049] When PS is within the above range, lithium ions are more likely to be smoothly inserted and removed from the surface of the primary particles, and the resistance of the lithium secondary battery can be reduced.
[0050] The PS of the CAM is determined from an image (SEM photograph) taken using a scanning electron microscope.
[0051] Specifically, first, a powder of a CAM sample is placed on a conductive sheet attached on a sample stage. Then, an image (SEM photograph) of the sample is taken by irradiating the sample with an electron beam at an acceleration voltage of 20 kV using a scanning electron microscope (SEM; for example, JSM-5510 manufactured by JEOL Ltd.). Then, the particle diameter of each of 50 primary particles randomly extracted from the image is measured. Here, the distance between a pair of parallel lines sandwiching the projected image of the primary particle (unidirectional diameter) is measured as the particle diameter. The arithmetic average value of the particle diameters of each of the primary particles is taken as PS. Note that if the number of primary particles is less than 50, other fields of view are observed until the number of primary particles reaches 50, and 50 primary particles are extracted.
[0052] [A-8] 50% cumulative volumetric particle size D50 CAM is the 50% cumulative volumetric grain size D 50 It is preferable that the relationship shown in the following (Formula G) is satisfied.
[0053] 5μm≦D 50 ≦30μm…(Formula G)
[0054] D 50 is preferably 6 μm or more, and more preferably 8 μm or more. 50 is preferably 25 μm or less, more preferably 20 μm or less. 50 is preferably 6-25 μm, more preferably 8-20 μm.
[0055] D 50 The CAM having the above range has a high bulk density and high packing property. In the positive electrode formed using such CAM, the contact area between the CAM particles and the conductive particles is increased, and the conductivity is increased. As a result, the resistance of the lithium secondary battery can be reduced.
[0056] In addition, D 50 (μm) corresponds to the particle diameter value at 50% accumulation from the fine particle side in the cumulative particle size distribution curve. 50 is measured by a laser diffraction scattering method.
[0057] Specifically, first, a dispersion liquid in which CAM powder is dispersed is obtained. The dispersion liquid is prepared by adding 0.1 g of CAM powder to 50 ml of sodium hexametaphosphate aqueous solution (concentration: 0.2% by mass). Next, a laser diffraction scattering particle size distribution measuring device (Microtrack MT3300EXII, manufactured by Microtrack Bell Co., Ltd.) is used to measure the particle size distribution of the powder in the dispersion liquid, thereby obtaining a cumulative particle size distribution curve based on volume. Then, from the cumulative particle size distribution curve, D 50 is required.
[0058] [A-9] 90% cumulative volumetric particle size D 90 and 10% cumulative volumetric grain size D 10 Relationship CAM is the 90% cumulative volumetric grain size D 90 and 10% cumulative volumetric grain size D 10 It is preferable that the relationship shown in the following (Formula H) is satisfied.
[0059] 1.6≦D 90 / D 10 ≦3.2 …(Formula H)
[0060] D 90 / D 10 is preferably 1.8 or more, and more preferably 2.0 or more. 90 / D 10 is preferably 3.1 or less, more preferably 3.0 or less. 90 / D 10 is preferably 1.8 to 3.1, and more preferably 2.0 to 3.0.
[0061] D 90 / D 10 In a positive electrode formed using CAM having a molecular weight in the above range, the CAM particles are easily packed densely, the contact area between the CAM particles and the conductive particles is increased, and the conductivity is increased, which results in a reduction in the resistance of the lithium secondary battery.
[0062] In addition, D 90 and D. 10 is calculated from the cumulative particle size distribution curve obtained above. 90 D corresponds to the particle size value at 90% cumulative accumulation from the fine particle side in the cumulative particle size distribution curve. 10 corresponds to the particle size value at 10% accumulation from the fine particle side in the cumulative particle size distribution curve.
[0063] [B]CAM manufacturing method The manufacturing method of the CAM will now be described.
[0064] When producing the CAM, a mixing step, a firing step, a post-treatment step, and a drying step are carried out in this order.
[0065] [B-1] Mixing process In the mixing process, a mixture of MCC, which is a precursor of CAM, and a lithium compound is prepared. The mixture may contain compounds other than MCC and the lithium compound, and may contain a zirconium compound (such as zirconium oxide).
[0066] The mixture contains MCC and a lithium compound such that the amount of substance of Li [Li], the amount of substance of Ni [Ni], and the amount of substance of the above element X [X] satisfy the relationships shown in the following (Equation J1) to (Equation J3) (a0 = [Li] / ([Ni] + [X])). That is, when manufacturing CAM having a desired amount of substance of Li (a in the above (Equation A1)), MCC and a lithium compound are mixed to obtain a mixture so as to satisfy the following (Equation J1) to (Equation J3). b in (Equation J1) is the same as b in the above (Equation A1).
[0067] [Li]:[Ni]:[X]=a0:(1 - b):b …(Equation J1) 0 < a0 - a ≦ 0.10 …(Equation J2) 1.05 ≦ a0…(Equation J3)
[0068] By using a mixture that satisfies the relationships shown in (Equation J1) to (Equation J3), CAM that satisfies the above (Equation B) and (Equation C) can be easily produced. As a result, the resistance of the lithium secondary battery can be reduced, and the oxygen release rate in the charged state can be reduced.
[0069] [B - 1 - 1]MCC MCC is a substance containing Ni and element X that constitute CAM, and is, for example, a metal composite hydroxide, a metal composite oxide, or a mixture thereof.
[0070] The metal composite hydroxide used as MCC is produced, for example, by a known batch coprecipitation method or a continuous coprecipitation method.
[0071] Hereinafter, taking a metal composite hydroxide containing Ni and element X as an example of the metal element, the manufacturing method will be described in detail.
[0072] Specifically, a nickel salt solution, a metal salt solution of element X, and a complexing agent are reacted by the continuous coprecipitation method described in JP-A-2002-201028. This produces a metal complex hydroxide (Ni (1-b) X b (OH)2 (b is the same as in formula A1 above) is produced.
[0073] The nickel salt that is the solute of the nickel salt solution is, for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate.
[0074] The metal salt that is the solute of the metal salt solution of element X is, for example, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese sulfate, manganese nitrate, manganese chloride, manganese acetate, aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum acetate.
[0075] The above metal salts are (Ni (1-b) X b (OH)2) in a ratio corresponding to the above. In this case, water is used as the solvent.
[0076] In the process for producing the metal composite hydroxide, a complexing agent may be used. In this case, the amount of the complexing agent is, for example, a molar ratio of more than 0 and not more than 2 to the total number of moles of the metal salts (nickel salt and metal salt of element X).
[0077] The complexing agent is a material capable of forming a complex with nickel ions and ions of element X in an aqueous solution. The complexing agent is, for example, at least one of an ammonium ion donor (ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc.), hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine.
[0078] In the co-precipitation method, an aqueous solution of an alkali metal hydroxide is added to a mixed solution containing a nickel salt solution, a metal salt solution of element X, and a complexing agent to adjust the pH value of the mixed solution before the pH of the mixed solution becomes neutral from alkaline. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.
[0079] In this case, the pH value is measured when the temperature of the mixed liquid is 40° C. If the temperature of the mixed liquid sampled from the reaction tank is not 40° C., the mixed liquid is heated or cooled to 40° C., and then the pH is measured.
[0080] In addition to the nickel salt solution and the metal salt solution of element X, a complexing agent is continuously fed to the reaction vessel, whereby the reaction takes place and (Ni (1-b) X b (OH)2) is produced.
[0081] The temperature of the reaction vessel is controlled, for example, within the range of 20-80°C, preferably within the range of 30-70°C.
[0082] During the reaction, the pH value of the mixture in the reaction tank is controlled within the range of, for example, 9-13.
[0083] The reaction precipitate formed in the reaction tank is neutralized under stirring for a period of time ranging from 1 to 20 hours, for example.
[0084] As a reaction vessel used in the continuous coprecipitation method, a reaction vessel having an overflow can be used in order to separate the formed reaction precipitate.
[0085] When producing a metal composite hydroxide by a batch coprecipitation method, a reaction tank without an overflow pipe or an apparatus having a mechanism for concentrating the overflowed reaction precipitate in a concentration tank connected to an overflow pipe and circulating it back to the reaction tank is used.
[0086] Here, various gases (for example, inert gases such as nitrogen, argon, or carbon dioxide, oxidizing gases such as air or oxygen, or a mixture thereof) may be supplied into the reaction vessel.
[0087] After the reaction is completed, the neutralized reaction precipitate is isolated. The isolation is carried out, for example, by dehydrating the slurry containing the reaction precipitate by centrifugation, suction filtration, etc. The reaction precipitate may also be washed before isolation.
[0088] The isolated reaction precipitate is then dried and sieved, if necessary, to obtain a metal composite hydroxide.
[0089] The reaction precipitate is preferably washed using water or an alkaline washing solution. In washing the reaction precipitate, an alkaline washing solution is preferably used, and in particular, an aqueous sodium hydroxide solution is preferably used as the alkaline washing solution. Washing may also be performed using a washing solution containing elemental sulfur. The washing solution containing elemental sulfur is, for example, an aqueous solution of potassium or sodium sulfate.
[0090] In the above example, a metal composite hydroxide is produced as MCC, but a metal composite oxide may also be prepared.
[0091] The metal composite oxide is produced, for example, by oxidizing a metal composite hydroxide (oxidation step). The oxidation step may be carried out multiple times as necessary. When multiple oxidation steps are carried out, the oxidation temperature means the temperature of the step in which oxidation is carried out at the highest temperature among the multiple oxidation steps.
[0092] The oxidation temperature is preferably in the range of 400-700° C., and more preferably in the range of 450-680° C. The oxidation temperature means the set temperature of the device used for oxidation.
[0093] The time for which the oxidation temperature is maintained in the oxidation step is preferably in the range of 0.1-20 hours, more preferably in the range of 0.5-10 hours. The heating rate when the temperature is increased to the oxidation temperature is, for example, in the range of 50-400° C. / hour. The oxidation step is carried out in an atmosphere containing, for example, air, oxygen, nitrogen, argon, or a mixed gas thereof.
[0094] The inside of the device used for oxidation may be an oxygen-containing atmosphere containing a moderate amount of oxygen. The oxygen-containing atmosphere may be a mixed gas atmosphere of an inert gas and oxygen, or an inert gas atmosphere in the presence of an oxidizing agent.
[0095] The oxygen-containing atmosphere need only have a sufficient amount of oxygen atoms present to oxidize the transition metal.
[0096] When the oxygen-containing atmosphere is a mixed gas atmosphere of an inert gas and oxygen, the atmosphere inside the apparatus is controlled by a method of passing oxygen through the apparatus or a method of bubbling oxygen into the mixed liquid.
[0097] The oxidizing agent may be a peroxide such as hydrogen peroxide, a peroxide salt such as permanganate, a perchlorate, a hypochlorite, nitric acid, a halogen, or ozone.
[0098] [B-1-2] Lithium compounds The lithium compound used in the production of CAM is, for example, at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, lithium chloride, and lithium fluoride. Of these, it is preferable to use at least one of lithium hydroxide, lithium hydroxide monohydrate, and lithium carbonate as the lithium compound.
[0099] [B-2] Firing process In the firing step, the mixture prepared in the mixing step is fired to produce a fired product.
[0100] The firing temperature is preferably in the range of 650-900°C, more preferably in the range of 680-850°C, and even more preferably in the range of 700-820°C. When the firing temperature is 650°C or higher, a CAM having a strong crystal structure can be obtained. Also, when the firing temperature is 900°C or lower, the volatilization of lithium ions on the particle surface of the CAM can be reduced.
[0101] In addition, the PS of the resulting CAM can be controlled within the above range by adjusting the holding time during firing. As the holding time increases, the PS tends to increase.
[0102] The retention time during firing is preferably in the range of 3 to 50 hours, more preferably in the range of 4 to 20 hours. If the retention time during firing is 50 hours or less, it is possible to prevent a decrease in battery performance due to the volatilization of lithium ions. If the retention time during firing is 3 hours or more, the crystals are sufficiently developed, and the battery performance is excellent. The retention time during firing is appropriately adjusted depending on the type of transition metal element used and the type and amount of the precipitating agent.
[0103] The rate of temperature rise until the firing temperature is reached is preferably 80° C. / hour or more, more preferably 100° C. / hour or more, and even more preferably 150° C. / hour or more. The rate of temperature rise until the firing temperature is reached is calculated from the time from the start of temperature rise in the firing device until the firing temperature is reached.
[0104] The firing step preferably has a plurality of firing stages with different firing temperatures. For example, the firing step preferably has a first firing stage and a second firing stage in which firing is performed at a higher temperature than the first firing stage. Furthermore, the firing step may have firing stages with different firing temperatures and firing times.
[0105] The firing step is carried out in a firing atmosphere that may include air, oxygen, nitrogen, argon, or a mixture thereof, depending on the desired composition.
[0106] The mixture may be sintered in the presence of an inactive flux. The inactive flux may be added to such an extent that the initial capacity of the battery using the CAM is not impaired, and may remain in the sintered product. As the inactive flux, for example, those described in WO2019 / 177032A1 can be used.
[0107] The mixture may be pre-baked before the above-mentioned baking step. In the pre-baking step, the mixture is pre-baked at a temperature lower than the baking temperature in the baking step. The baking temperature in the pre-baking step is, for example, in the range of 400°C or higher and lower than 700°C. The holding time in the pre-baking step is, for example, 3 to 50 hours. The pre-baking step may be performed multiple times.
[0108] The firing apparatus used in the firing step and the pre-firing step is, for example, a continuous firing furnace or a fluidized firing furnace. The continuous firing furnace is, for example, a tunnel furnace or a roller hearth kiln. The fluidized firing furnace is, for example, a rotary kiln.
[0109] The fired product obtained in the firing step may be crushed as appropriate, thereby producing a crushed fired product.
[0110] The fired product may be crushed multiple times. For example, when the firing step involves sequentially performing a first firing stage and a second firing stage, the fired product may be crushed after the first firing stage and then crushed again after the second firing stage.
[0111] [B-4] Post-processing process In the post-treatment process, the fired product produced in the firing process is subjected to post-treatment. Examples of the post-treatment include washing the fired powder with a washing solution such as water, ion-exchanged water, an alkaline aqueous solution, or a sulfate aqueous solution to remove impurities. Specifically, the fired product is mixed with the washing solution and dehydrated to obtain a slurry. In the post-treatment, the slurry concentration is set to less than 40% by weight, and the washing time is within a predetermined range. The washing time is preferably 5 to 20 minutes. The slurry concentration refers to the ratio of the weight of the fired product (WS) to the total weight (WS+WL) of the fired product (WS) and the washing solution (WL) (i.e., 100*WS / (WS+WL)).
[0112] By adjusting the conditions in the post-treatment process, it is possible to easily prepare a CAM that satisfies the above formulas B and C. As a result, the resistance of the lithium secondary battery can be reduced, and the oxygen release rate in the charged state can be reduced.
[0113] [B-5] Drying process In the drying step, the slurry is dried.
[0114] In the drying step, the fired product is preferably dried in an atmosphere having a temperature in the range of 100-400°C. The drying temperature is preferably equal to or higher than the lower limit of the above range in order to prevent a decrease in the charge capacity of the lithium secondary battery due to moisture remaining in the CAM before drying. The lower limit of the drying temperature is more preferably 110°C, and even more preferably 120°C or higher. Moreover, the drying temperature is preferably equal to or lower than the upper limit of the above range in order to prevent re-sintering of the grain boundaries of the CAM. The upper limit of the drying temperature is more preferably 350°C, and even more preferably 300°C.
[0115] The drying is performed, for example, by reduced pressure drying, vacuum drying, air blowing, heating, or a combination of these. Reduced pressure drying and vacuum drying are performed, for example, under conditions of 0.3 atm or less and a temperature range of 100-200° C. Drying by air blowing is performed, for example, using a hot air dryer.
[0116] [B-6] Covering layer formation process As an optional step, the dried powder may be mixed with a coating material raw material and heat-treated. The coating material raw material may be, for example, an oxide, hydroxide, carbonate, sulfate, nitrate, halide, oxalate, or alkoxide of at least one element selected from the group consisting of Nb, Ge, Si, P, Al, W, Ta, Ti, S, Zr, Zn, V, and B, and is preferably an oxide.
[0117] The heat treatment conditions are adjusted according to the type of the coating material raw material. For example, the heat treatment temperature is in the range of 200-850°C, and the heat treatment time is in the range of 3 hours to 50 hours. The atmosphere during the heat treatment can be air, oxygen, nitrogen, argon, or a mixture of these gases.
[0118] Through the above steps, the CAM can be manufactured.
[0119] [C] Battery evaluation The battery evaluation of CAM will be explained.
[0120] [C-1] DC resistance R The resistance of a lithium secondary battery is evaluated by the value of "DC resistance R." The "DC resistance R" is obtained by producing a lithium secondary battery using CAM according to the following procedure and measuring it using the following method.
[0121] The above items will be explained in detail below.
[0122] [C-1-1] Preparation of positive electrode In the preparation of the positive electrode, first, a paste-like positive electrode mixture is prepared. The positive electrode mixture is prepared by kneading a mixture of CAM, a conductive material, and a binder. Here, acetylene black is used as the conductive material, and PVdF is used as the binder. Then, each material is mixed in the following ratio. When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as the organic solvent.
[0123] ·CAM: 92 parts by mass ·Conductive material: 5 parts by mass Binder: 3 parts by weight
[0124] The paste-like positive electrode mixture prepared as above is applied to a current collector (aluminum foil with a thickness of 40 μm). The current collector to which the positive electrode mixture is applied is then vacuum-dried for 8 hours in an atmosphere at a temperature of 150° C. to complete the positive electrode. The electrode area of the positive electrode is 1.65 cm2. 2 It is.
[0125] [C-1-2] Fabrication of coin-type full-cell lithium secondary batteries The positive electrode prepared above is placed on the upper surface of the bottom cover of a coin-type battery CR2032 part (manufactured by Hosen Co., Ltd.). When installing it on the bottom cover, the aluminum foil surface of the positive electrode faces downward. Then, a separator is installed on the upper surface of the bottom cover on which the positive electrode is installed. A porous polyethylene film is used as the separator.
[0126] Next, 300μl of electrolyte is injected into the inside of the above part. The electrolyte is a solution in which the following materials are mixed in the following ratio, to which 1% by volume of vinylene carbonate is added, and further LiPF6 is dissolved. The electrolyte is prepared so that the concentration of LiPF6 is 1mol / l.
[0127] Ethylene carbonate: 16 parts by volume Dimethyl carbonate: 10 parts by volume Ethyl methyl carbonate: 74 parts by volume
[0128] Next, the negative electrode is placed on the top of the separator. Here, a graphite particle coated electrode foil (graphite particle weight 98% of the total weight of the coated electrode foil) is used as the negative electrode. Then, a top cover is placed via a gasket, and the top cover is crimped using a crimping machine. This completes the manufacture of a coin-type full-cell CR2032 lithium secondary battery.
[0129] [C-1-3] Formation process The lithium secondary battery produced as described above is subjected to a formation step.
[0130] In the formation process, first, the initial charge and discharge are performed. In the initial charge and discharge, the upper limit voltage is set to 3.5V and constant current charging is performed at 0.01 CA, then the upper limit voltage is set to 4.2V and constant current constant voltage charging is performed at 0.05 CA, and then the lower limit voltage is set to 2.5V and constant current discharging is performed at 0.1 CA.
[0131] After the initial charge and discharge in the formation process, the upper limit voltage is set to 4.2 V and the lower limit voltage is set to 2.5 V, and two cycles of constant current / constant voltage charging at 0.1 CA and constant current discharging at 0.1 CA are repeated, followed by three cycles of constant current / constant voltage charging at 0.2 CA and constant current discharging at 0.2 CA.
[0132] [C-1-4] Measurement of DC resistance R Next, the lithium secondary battery that has undergone the formation process is subjected to a pre-measurement process. In the pre-measurement process, the battery is charged at 4.2 V, with the discharge capacity at 1 CA being 100% in a voltage range with an upper limit voltage of 4.2 V and a lower limit voltage of 2.5 V, and then a constant current discharge is performed at 1 CA so that the remaining capacity is 60%. Then, the open circuit voltage of the lithium secondary battery that has undergone the pre-measurement process when no current is applied is measured.
[0133] Then, a constant current is applied to the lithium secondary battery that has been subjected to the pre-measurement treatment, and the voltage is measured 10 seconds after the application of the current. Then, the voltage drop ΔV relative to the open circuit voltage is calculated from the voltage value. Here, the above-mentioned voltage drop ΔV is obtained for each condition where the constant current is 2 mA, 4 mA, 8 mA, and 16 mA. Then, the DC resistance R in the low charge state is calculated using a linear function equation ΔV=R×ΔI relating to each current ΔI, DC resistance R, and voltage drop ΔV. The test temperature is 25° C. In this embodiment, the measured value of the DC resistance R obtained in Example 1 described later is set to a relative value of 100%, and the DC resistance values obtained in other examples and comparative examples are converted to relative values based on the value of Example 1.
[0134] The smaller the value of the DC resistance R, the more the resistance of the lithium secondary battery is reduced. In this embodiment, when the relative value of the DC resistance R exceeds 105%, the internal resistance of the battery is large, so that the voltage drop is large when the discharge current is increased, making it difficult to obtain the desired voltage from the battery. For this reason, when the DC resistance R is 105% or less, it is determined that the resistance is reduced.
[0135] [C-2] Peak oxygen release velocity VP The oxygen release rate of a lithium secondary battery is evaluated by the value of "peak oxygen release rate VP." The "peak oxygen release rate VP" can be determined by disassembling a lithium secondary battery prepared according to the following procedure after charging it, extracting the positive electrode mixture containing CAM, and performing simultaneous thermogravimetry and differential thermal analysis on the extracted positive electrode mixture.
[0136] The above items will be explained in detail below.
[0137] [C-2-1] Fabrication of coin-type half-cell lithium secondary batteries First, the positive electrode prepared above is placed on the upper surface of the bottom cover of a coin-type battery R2032 part (manufactured by Hosen Co., Ltd.). When placing it on the bottom cover, the aluminum foil surface of the positive electrode faces downward. Then, a separator is placed on the upper surface of the bottom cover on which the positive electrode is placed. A porous polyethylene film is used as the separator.
[0138] Next, 300μl of electrolyte is injected into the inside of the above part. The electrolyte is a solution in which LiPF6 is dissolved in a mixture of the following substances in the following ratio. The electrolyte is prepared so that the concentration of LiPF6 is 1mol / l.
[0139] Ethylene carbonate: 30 parts by volume Dimethyl carbonate: 35 parts by volume Ethyl methyl carbonate: 35 parts by volume
[0140] Next, the negative electrode is placed on the top of the separator. Metallic lithium is used as the negative electrode. Then, the top cover is placed via a gasket and the top cover is crimped using a crimping machine. This completes the lithium secondary battery, which is a coin-type half-cell R2032.
[0141] [C-2-2]Charging and discharging The lithium secondary battery is subjected to an "initial charge / discharge" under the following (initial charge / discharge conditions) and then a "second charge".
[0142] (Initial charge / discharge conditions) Processing temperature: 25℃ Maximum charging voltage: 4.3V, charging current: 0.1C, constant current / constant voltage charging, end current: 0.025C Minimum discharge voltage: 2.5V, discharge current: 0.1C, constant current discharge
[0143] (Second charge) Maximum charging voltage 4.3V, charging current 0.1C, constant current constant voltage charging, end current 0.025C
[0144] [C-2-3] Demolition In a glove box filled with argon gas, the lithium secondary battery is disassembled using a dismantling machine so as not to short-circuit the positive and negative electrodes of the charged lithium secondary battery, and the positive electrode is removed from the lithium secondary battery.
[0145] [C-2-4] Extraction of positive electrode mixture The positive electrode removed from the lithium secondary battery is washed to remove the electrolyte adhering to the positive electrode. Dimethyl carbonate (DMC) is used as the washing solution for washing. The washed positive electrode is then dried to remove the washing solution adhering to the positive electrode. After that, in a glove box with an argon gas atmosphere, the positive electrode mixture containing CAM is collected from the positive electrode. To collect the positive electrode mixture, the positive electrode mixture applied to the Al foil on the positive electrode is scraped off using ceramic tweezers.
[0146] [C-2-5] Simultaneous thermogravimetry and differential thermal analysis The positive electrode mixture obtained above is subjected to simultaneous thermogravimetry and differential thermal analysis under the following conditions using a simultaneous thermogravimetry and differential thermal analysis measuring device (STA7300; Hitachi High-Tech Corporation). By measuring at a heating temperature of 400°C or less under a nitrogen gas flow, only the CAM thermally decomposes without causing decomposition of the conductive material and binder in the positive electrode mixture, and the thermogravimetric loss associated with the release of oxygen from the CAM can be measured.
[0147] · Upper limit of measurement temperature: 400℃ Heating rate: 5℃ / min Measurement atmosphere: Nitrogen gas flow · Weight of positive electrode mixture set: 10mg Measuring container: Metal aluminum pan
[0148] This allows the thermogravimetric curve (TG curve) to be obtained.
[0149] [C-2-6] Calculation of peak oxygen release velocity VP The peak oxygen release velocity VP is calculated from the TG curve obtained as described above.
[0150] Fig. 1A is a diagram showing an example of a TG curve, in which the horizontal axis indicates time t (min) and the vertical axis indicates the percentage TG (%) of the weight of the sample reduced relative to the initial weight.
[0151] 1B is a diagram showing an oxygen release rate curve obtained by differentiating the TG curve with respect to time t. In FIG 1B, the horizontal axis represents time t (min), and the vertical axis represents the oxygen release rate ΔTG / Δt (% / min).
[0152] When simultaneous thermogravimetry and differential thermal analysis is performed, oxygen (O2) is released from the sample, and as time t passes, the weight of the sample decreases, as shown in Figure 1A. For this reason, as shown in Figure 1B, the oxygen release rate ΔTG / Δt is calculated, and the maximum value of the oxygen release rate ΔTG / Δt is determined as the peak oxygen release rate VP. The smaller VP is, the more the oxygen release rate has been reduced. When a charged CAM is heated to 400°C, it can release oxygen while causing a total weight loss of about 15%. When the rate at which VP loses weight relative to the initial weight is 1.5% / min or more, 10% or more of the total amount of oxygen is instantaneously released under certain heating temperature conditions. For this reason, when VP is less than 1.5% / min, it is determined that the oxygen release rate is decreasing.
[0153] [D] Lithium secondary battery An example of a positive electrode for a lithium secondary battery using CAM and a lithium secondary battery including the positive electrode for a lithium secondary battery will be described below. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode.
[0154] An example of a suitable lithium secondary battery when using the CAM manufactured by the manufacturing method of this embodiment has a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0155] 2 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0156] 2, a pair of belt-shaped separators 1, a belt-shaped positive electrode 2 having a positive electrode lead 21 attached to one end, and a belt-shaped negative electrode 3 having a negative electrode lead 31 attached to one end are prepared. Then, the separator 1, the positive electrode 2, the separator 1, and the negative electrode 3 are laminated in this order to form a laminate, which is then wound to produce an electrode group 4.
[0157] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.
[0158] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.
[0159] Next, the electrode group 4 and the insulator (not shown) are housed in a battery can 5, and the bottom of the battery can 5 is sealed. Then, the electrode group 4 is impregnated with an electrolyte solution 6 in the battery can 5, thereby interposing an electrolyte (not shown) between the positive electrode 2 and the negative electrode 3. Thereafter, the top of the battery can 5 is sealed with a top insulator 7 and a sealing body 8. In this way, a lithium secondary battery 10 is completed.
[0160] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0161] The shape of the lithium secondary battery having such an electrode group 4 may be any shape specified by IEC60086, a standard established by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes may be used.
[0162] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.
[0163] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in
[0113] to
[0140] of WO2022 / 113904A1 can be used.
[0164] [E] All-solid-state lithium secondary battery As an example of a lithium secondary battery including a positive electrode for a lithium secondary battery using the CAM of this embodiment, an all-solid-state lithium secondary battery will be described.
[0165] FIG. 3 is a schematic diagram showing an example of an all-solid-state lithium secondary battery.
[0166] As shown in Fig. 3, the all-solid-state lithium secondary battery 1000 includes a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may have a bipolar structure in which a CAM and a negative electrode active material are disposed on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400.
[0167] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.
[0168] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.
[0169] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0170] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200, and a sealing body (not shown) that seals the opening 200a of the exterior body 200.
[0171] Exterior body 200 is a container formed from a highly corrosion-resistant metal material such as aluminum, stainless steel, nickel-plated steel, etc. Exterior body 200 may also be a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant.
[0172] The shape of the all-solid-state lithium secondary battery 1000 may be, for example, a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, or a laminate type (pouch type).
[0173] As an example, the all-solid-state lithium secondary battery 1000 has one laminate 100, but is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminates 100) are sealed inside the exterior body 200.
[0174] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in
[0151] to
[0181] of WO2022 / 113904A1 can be used. EXAMPLES
[0175] Examples and comparative examples will be described below with reference to Tables 1 and 2. In Tables 1 and 2, (Example 1) to (Example 4) correspond to examples, and (Example C1) to (Example C4) correspond to comparative examples.
[0176] [Table 1]
[0177] [Table 2]
[0178] [1] Sample preparation The procedure for preparing the CAM samples for each example will be described in turn.
[0179] (Example 1) As MCC1, nickel-cobalt-manganese metal composite hydroxide (composition formula: Ni 0.83 Co 0.12 Mn 0.05 A powder of MCC1 was prepared by the sequential co-precipitation method described in JP-A-2002-201028.
[0180] Next, a powder of lithium hydroxide monohydrate prepared as a lithium compound, a powder of MCC1, and a powder of zirconium oxide were mixed together to obtain a mixture 1.
[0181] Here, the mixture was mixed so that the value a0 obtained by dividing [Li] by the sum of [Ni] and [X] (in this example, the amount of substance of Co [Co], the amount of substance of Mn [Mn], and the amount of substance of Zr [Zr]) in the mixture would be the value shown in Table 1. (In other words, a0 = [Li] / ([Ni] + [X]) = [Li] / ([Ni] + [Co] + [Mn] + [Zr])).
[0182] Mixture 1 was packed into a sagger, and then pre-fired in an oxygen atmosphere at a temperature of 650° C. for 2 hours, and then the temperature was further increased and fired at a temperature of 750° C. for 5 hours.
[0183] The obtained fired product 1 was crushed.
[0184] Next, the crushed fired material 1 and pure water were mixed in a weight ratio of 1:1 and stirred for 20 minutes to dehydrate, thereby preparing a slurry. At this time, the slurry concentration was 50% by weight. The slurry was then dried at 190°C to obtain a powder 1.
[0185] ·Coating layer formation process Then, Powder 1 was mixed with boric acid powder. The mixing was carried out at a ratio such that the amount of B contained in boric acid [B] divided by the sum of the amounts of [Ni] and [X] contained in Powder 1 was 1 mol%.
[0186] Then, the mixed powder of Powder 1 and boric acid powder was filled into a sagger, and heat-treated at 300° C. for 5 hours in an oxygen gas atmosphere to obtain a sample of CAM1.
[0187] (Example 2) A powder of lithium hydroxide monohydrate prepared as a lithium compound, a powder of MCC1, and a powder of zirconium oxide were mixed so that a0 had a value shown in Table 1. The same procedure as in Example 1 was carried out to prepare a sample of CAM2.
[0188] (Example 3) Nickel-cobalt-aluminum metal composite hydroxide (composition formula: Ni 0.88 Co 0.09 Al 0.03 The nickel-cobalt-aluminum metal composite hydroxide was prepared by the continuous coprecipitation method described in JP-A-2002-201028. The nickel-cobalt-aluminum metal composite hydroxide was then oxidized at 650°C in an air atmosphere to obtain nickel-cobalt-aluminum metal composite oxide (composition formula: Ni 0.88 Co 0.09 Al 0.03 O) powder was obtained.
[0189] Next, a powder of lithium hydroxide monohydrate prepared as a lithium compound was mixed with a powder of MCC2 to obtain a mixture 3.
[0190] At this time, mixing was performed so that the value a0 obtained by dividing [Li] by the sum of [Ni] and [X] (= the amount of Al, [Al], and [Co]) in mixture 3 became the value shown in Table 1. (That is, a0=[Li] / ([Ni]+[Co]+[Al])).
[0191] A sample of CAM3 was produced in the same manner as in Example 1, except that Mixture 3 was used, the firing temperature was set to 740° C., and the coating layer forming step was not performed.
[0192] (Example 4) As MCC4, nickel-cobalt-manganese-metal composite hydroxide (composition formula: Ni 0.88 Co 0.09 Mn 0.03 A powder of MCC4 (OH) was prepared. The preparation of MCC4 was carried out by the continuous co-precipitation method described in JP-A-2002-201028.
[0193] Next, a sample of CAM4 was prepared in the same manner as in Example 1, except that a powder of lithium hydroxide monohydrate prepared as a lithium compound, a powder of MCC4, and a powder of zirconium oxide were mixed so that a0 had a value shown in Table 1.
[0194] (Example C1) A powder of lithium hydroxide monohydrate prepared as a lithium compound and a powder of MCC1 were mixed so that a0([Li] / ([Ni]+[Co]+[Mn])) had the value shown in Table 2 to obtain mixture 5. Mixture 5 was filled into a sagger and then pre-fired for 2 hours at a temperature of 650°C in an oxygen atmosphere, and then the temperature was raised to 820°C and fired for 5 hours.
[0195] The obtained fired product 5 was crushed. The above-mentioned coating layer forming step in (Example 1) was carried out using the crushed fired product 5 to prepare a sample of CAM5.
[0196] (Example C2) A sample of CAM6 was produced in the same manner as in Example 1, except that a powder of lithium hydroxide monohydrate prepared as a lithium compound, a powder of MCC1, and zirconium oxide were mixed so that a0 had the value shown in Table 2, the firing temperature was set to 740°C, and the slurry concentration was set to 40% by weight.
[0197] (Example C3) MCC7 is a nickel-cobalt-manganese metal composite hydroxide (composition formula: Ni 0.88 Co 0.08 Mn 0.04 A powder of MCC7 (OH) was prepared. The preparation of MCC7 was carried out by the continuous co-precipitation method described in JP-A-2002-201028.
[0198] Next, a powder of lithium hydroxide monohydrate prepared as a lithium compound was mixed with a powder of MCC7 so that a0([Li] / ([Ni]+[Co]+[Mn])) was the value shown in Table 2, and potassium sulfate was further mixed in so that the molar ratio was [K] / ([Li]+[K]) = 0.1, the firing temperature was 820°C, the slurry concentration was 30% by weight, and a sample of CAM7 was produced in the same manner as in Example 1, except that the coating layer formation process was not performed.
[0199] (Example C4) A powder of lithium hydroxide monohydrate prepared as a lithium compound and a powder of MCC1 were mixed so that a0 had the value shown in Table 2 to obtain a mixture 8. After filling a sagger, the mixture 8 was pre-fired in an oxygen atmosphere at a temperature of 650°C for 2 hours, and then the temperature was raised and the mixture was fired at a temperature of 750°C for 5 hours. The obtained fired product 8 was crushed to prepare a sample of CAM8.
[0200] [2] Characteristics of the sample The properties of the CAM samples prepared for each example as described above were determined as shown in Tables 1 and 2.
[0201] [2-1]d, WA / WB, WB, HB / HC For each sample, the values of d, WA / WB, WB, and HB / HC were determined according to the methods described in sections [A-3] to [A-6] above.
[0202] [2-2] P.S. For each sample, the PS value was determined according to the method described in section [A-7] above.
[0203] [2-3]D 50 ,D 90 / D 10 For each sample, D 50 , and D. 90 / D 10 The value was determined according to the methods described in columns [A-8] and [A-9] above.
[0204] [2-4] Crystal structure The crystal structure of each sample was confirmed according to the method described in section [A-1] above.
[0205] [2-5] Composition The crystal structure of each sample was analyzed according to the method described in section [A-2] above.
[0206] [3] DC resistance R, peak oxygen release velocity VP As described above, for the CAM samples prepared in each example, R and VP were measured as shown in Tables 1 and 2. These were performed according to the method described above in “[C] Battery Evaluation.”
[0207] [4] Summary The results of each example are explained.
[0208] [4-1] Regarding (Example 1) to (Example 4) The samples of (Example 1) to (Example 4) have a NaFeO2 type crystal structure and satisfy the relationships shown in the above-mentioned (Formula A1) to (Formula A3) as well as the relationships shown in (Formula B) to (Formula H).
[0209] As a result, it was confirmed that (Example 1) to (Example 4) had a DC resistance R equal to or less than the standard value and a peak oxygen release velocity VP less than the standard value, as shown in Table 1, and thus had good performance.
[0210] [4-2] Regarding (Example C1) to (Example C4) (Example C1) to (Example C4) have a NaFeO2 type crystal structure, but unlike (Example 1) to (Example 4), they do not satisfy at least one of the relationships shown in (Formula A1), (Formula A2), (Formula A3), (Formula B), and (Formula C).
[0211] As a result, unlike (Example 1) to (Example 4), (Example C1) to (Example C4) do not satisfy the relationship with the standard value for at least one of the DC resistance R and the peak oxygen release velocity VP, as shown in Table 1. As a result, it was found that (Example C1) to (Example C4) are inferior in performance to (Example 1) to (Example 4). [Industrial Applicability]
[0212] According to the present invention, it is possible to provide a CAM, a positive electrode for a lithium secondary battery, and a lithium secondary battery that are capable of reducing the resistance of a lithium secondary battery and reducing the oxygen release rate when oxygen is released in a charged state. [Explanation of symbols]
[0213] 1...separator, 2...positive electrode, 2a...positive electrode active material layer, 2b...positive electrode current collector, 3...negative electrode, 4...electrode group, 5...battery can, 6...electrolyte, 7...top insulator, 8...sealing body, 10...lithium secondary battery, 21...positive electrode lead, 31...negative electrode lead, 100...laminated body, 110...positive electrode, 111...positive electrode active material layer, 112...positive electrode current collector, 113...external terminal, 120...negative electrode, 121...negative electrode active material layer, 122...negative electrode current collector, 123...external terminal, 130...solid electrolyte layer, 200...exterior body, 200a...opening, 1000...all-solid-state lithium secondary battery
Claims
1. The composition contains Li, Ni, and an element X, The element X is at least one element selected from the group consisting of Co, Mn, Al, Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, and B; NaFeO 2 having a type crystal structure, A positive electrode active material for a lithium secondary battery, comprising: The amount of substance of Li [Li], the amount of substance of Ni [Ni], and the amount of substance of element X [X] satisfy the relationships shown in the following (Formula A1) to (Formula A3), In the powder X-ray diffraction spectrum using CuKα radiation, The spacing d of the lattice planes determined from the diffraction peak A assigned to the (110) plane satisfies the relationship shown in the following (Formula B), The half width WA of the diffraction peak A and the half width WB of the diffraction peak B assigned to the (003) plane satisfy the relationship shown in the following (Formula C), Positive electrode active material for lithium secondary batteries. [Li]:[Ni]:[X]=a:(1-b):b...(Formula A1) 1.0≦a≦1.2...(Formula A2) 0<b≦0.3...(Formula A3) 1.4325Å≦d≦1.4355Å…(Formula B) 1.6≦WA / WB≦2.3…(Formula C)
2. The half width WB of the diffraction peak B satisfies the relationship shown in the following (Formula D), The positive electrode active material for a lithium secondary battery according to claim 1 . 0.16°≦WB≦0.18°…(Formula D)
3. In the powder X-ray diffraction spectrum, a height HB of the diffraction peak B and a height HC of the diffraction peak C assigned to the (006) plane satisfy the relationship shown in the following (Formula E): The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 3.0≦HB / HC≦4.5…(Formula E)
4. The average primary particle diameter PS satisfies the relationship shown in the following (Formula F), The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 0.05μm≦PS≦1μm…(Formula F)
5. 50% cumulative volumetric particle size D 50 satisfies the relationship shown in the following (Formula G), The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 5μm≦D 50 ≦30μm …(Formula G)
6. 90% cumulative volumetric particle size D 90 and 10% cumulative volumetric grain size D 10 and satisfy the relationship shown in the following (Formula H), The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 1.6≦D 90 / D 10 ≦3.2 …(Formula H)
7. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, Positive electrode for lithium secondary batteries.
8. The positive electrode for a lithium secondary battery according to claim 7, Lithium secondary battery.
Citation Information
Patent Citations
Positive electrode active material for nonaqueous rechargeable battery, and nonaqueous electrolyte rechargeable battery
WO2018043190A1